Can macular xanthophylls replace cholesterol in formation of the liquid-ordered phase in lipid-bilayer membranes? - Subczynski, Witold K. (2012)
Lateral organization of membranes made from binary mixtures of dimyristoylphosphatidylcholine (DMPC) or dipalmitoylphosphatidylcholine (DPPC) and macular xanthophylls (lutein or zeaxanthin) was investigated using the saturation-recovery (SR) EPR spin-labeling discrimination by oxygen transport (DOT) method in which the bimolecular collision rate of molecular oxygen with the nitroxide spin label is measured. This work was undertaken to examine whether or not lutein and zeaxanthin, macular xanthophylls that parallel cholesterol in its function as a regulator of both membrane fluidity and hydrophobicity, can parallel other structural functions of cholesterol, including formation of the liquid-ordered phase in membranes. The DOT method permits discrimination of different membrane phases when the collision rates (oxygen transport parameter) differ in these phases. Additionally, membrane phases can be characterized by the oxygen transport parameter in situ without the need for separation, which provides information about the dynamics of each phase. In gel-phase membranes, two coexisting phases were discriminated in the presence of macular xanthophylls—namely, the liquid-ordered-like and s(o) phases. However, in fluid-phase membranes, xanthophylls only induce the solitary liquid-ordered-like phase, while at similar concentrations, cholesterol induces coexisting liquid-ordered and liquid-disordered phases. No significant differences between the effects of lutein and zeaxanthin were found.